St. Petersburg’s Myth. Standard of Hyper Reality and Secondary Culture - Bartov, Arkadij A. (Respectus Philologicus, 2003)
The epoch of hyperreality and postmodernism is usually understood as formation of communicative information nets making image, picture, sign, and idea more visual, tangible and real than the things that are denoted or reflected. Essentially, such formation of artificial reality, though in lesser scale than in Soviet and post-Soviet times, has long become the prerogative of the history of Russia. The method of simulation of all achievements of European civilization, which found its acme in foundation and development of St. Petersburg, turned out to be very productive in Russia. It is pointed out that the celebration devoted to the 300th anniversary of St. Petersburg has vividly demonstrated how simulation of reality becomes the standard of hyperrealism. Entering New Times, Russia surpassed the West in its postmodernist quality, that is, in secondary culture, conscious and unconscious as well, in imitation, simulation. It is revealed in the most distinct and concentrated form in the history and culture of St. Petersburg and in the myth accompanying it.